2018
DOI: 10.1007/s13595-018-0770-2
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometric analyses of leaf shapes in two sympatric Chinese oaks: Quercus dentata Thunberg and Quercus aliena Blume (Fagaceae)

Abstract: & Key message Geometric morphometric analyses (GMMs) of the leaf shape can distinguish two congeneric oak species Quercus dentata Thunberg and Quercus aliena Blume in sympatric areas. & Contexts High genetic and morphological variation in different Quercus species hinder efforts to distinguish them. In China, Q. dentata and Q. aliena are generally sympatrically distributed in warm temperate forests, and share some leaf morphological characteristics. & Aims The aim of this study was to use the morphometric meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 70 publications
2
48
0
Order By: Relevance
“…A total of 382 mature leaves from 139 red birch individuals and 218 leaves from 74 white birch individuals were scanned using a Hewlett-Packard printer (LaserJet Pro MFP M128fn) with a resolution of 600 d.p.i. Thirteen landmarks were selected from each scanned leaf as described in previous studies (Jensen et al , 2002; Viscosi et al , 2009; Liu et al , 2018). These were: the distal tip of petiole (1), the junction between the petiole and the leaf blade (2), the first serration on the right-hand side of the leaf (3), the right-hand point of one-fifth of the leaf from the lower side (4), the right-hand point of the widest part of leaf (5), the right-hand point of three-fifths of the leaf from the lower side (6), the right-hand point of four-fifths of each leaf from the lower side (7), the leaf tip (8), the left-hand point of four-fifths of the leaf from the lower side (9), the left-hand point of three-fifths of the leaf from the lower side (10), the left-hand point of the widest part of the leaf (11), the left-hand point of one-fifth of the leaf from the lower side (12) and the first serration on the left-hand side of the leaf (13) (Supplementary Data, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 382 mature leaves from 139 red birch individuals and 218 leaves from 74 white birch individuals were scanned using a Hewlett-Packard printer (LaserJet Pro MFP M128fn) with a resolution of 600 d.p.i. Thirteen landmarks were selected from each scanned leaf as described in previous studies (Jensen et al , 2002; Viscosi et al , 2009; Liu et al , 2018). These were: the distal tip of petiole (1), the junction between the petiole and the leaf blade (2), the first serration on the right-hand side of the leaf (3), the right-hand point of one-fifth of the leaf from the lower side (4), the right-hand point of the widest part of leaf (5), the right-hand point of three-fifths of the leaf from the lower side (6), the right-hand point of four-fifths of each leaf from the lower side (7), the leaf tip (8), the left-hand point of four-fifths of the leaf from the lower side (9), the left-hand point of three-fifths of the leaf from the lower side (10), the left-hand point of the widest part of the leaf (11), the left-hand point of one-fifth of the leaf from the lower side (12) and the first serration on the left-hand side of the leaf (13) (Supplementary Data, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is an important relict vegetation of temperate forests and culturally important sites. It is an instantly recognizable facet of Korean heritage [3], and an important forestry species in Northern China [4] commonly used as landscape trees [5]. Its wood is a good material for building boats, furniture and wood flooring for houses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Q. aliena and Q. dentata are sympatrically distributed in a wide range in warm temperate forests of East Asia. The two species overlap at flowering time, which facilitates the introgression and hybridization between the two species [4]. A chloroplast DNA polymorphism study in four oak species (Q. serrata, Q. mongolica var.…”
Section: Introductionmentioning
confidence: 99%
“…For Quercus , Liu et al (2018) conducted a study with the aim to identify two sympatric species and their hybrid, preliminarily identified from molecular markers. The discrimination rate for the morphometrical data turned out to be 96.9 and 95.9% for respectively species.…”
Section: Discussionmentioning
confidence: 99%